Girls and Rape Culture. Issue 1 (1st March 2021) - Harde, Roxanne
Abstract : In 1983, Andrea Dworkin addressed the Midwest Men's Conference in Minneapolis. She discussed the rape culture in which we live, noted the similarities between rape and war, and, following the title of her talk, asked for a "24-hour truce in which there is no rape." And she asked why men and boys are so slow to understand that women and girls "are human to precisely the degree and quality that [they] are" (n.p.). Every sexual assault begins with the dehumanization of the victim. And sometimes, after the violation, after the pain and the fear, comes the institutional dehumanization visited upon the victim who seeks medical or legal help. Two recent memoirs bring to the surface rape culture, evident in the young men who raped these girls and the systemic dehumanization they suffered when they sought justice. Chanel Miller's Know My Name (2019) describes the aftermath of being sexually assaulted, when she was just out of college and still living at home, by someone she met at a fraternity party. Although the case against her rapist was as strong as possiblethere were eyewitnesses and physical evidence was collected immediatelyhe was sentenced to only six months in the county jail, and she was repeatedly shamed, her humanity denied by the judicial system. Lacy Crawford's Notes on a Silencing (2020) describes the aftermath of being sexually assaulted, when she was 15, by two boys, students at her New England boarding school, including an account of how school officials refused to do anything other than label her promiscuous and protect the boys. The ways in which she was silenced by St. Paul's, which disregarded her health and future, and denied her humanity because she was only a girl, were profound. In both cases, the promising future of the perpetrators was prioritized over the humanity of the girls by many institutions, including the judiciary and the press. Crawford was raped just seven years after Dworkin made her plea to that men's conference, but Miller was assaulted twenty-five years after, making perfectly clear that rape culture has become only more entrenched.